Maximum Power Point Box (MPPB) Design to Advance BIPV Installations on Residential Properties - Mohamad Nassereddine; Chadi Nohra (IAES Indonesian Section, 2021)
Photovoltaic installations on residential properties gained high momentums during the past decade. Building integrated photovoltaic materials are well developed and has the potential to advance the photovoltaic systems installations on residential and commercial buildings. One of the main limitations on residential system is the utility allowable AC power generation. The installation of BIPV on houses offer numerous orientation and tilts of the PV system which ensure sun energy is harvested for wider timeframe. The different orientations and tilts reflect changes in the generate output power. The available residential inverters have one of two MPPTs which limit the orientation and tilts of the system to a maximum of two options per inverter. Adding more inverters will add cost burden on the system, exceed the utility maximum allowable AC power generation, and additional inverters will not work at rated power throughout the day. The works in this paper include the detail design of a maximum power point box (MPPB) that harvest the sun energy for different orientations and tilts, manage and regulate the DC Bus Bar voltage level as well as generated DC power prior the inverter input terminal. The process is governed by an input from the inverter using an industrial communication protocol such as MODBUS. The aim of the box is to reduce the number of inverters required for maximum power generation while maintaining the maximum AC limits set the by utilities. The paper includes the details design with the proposed circuit along its optimum logics. Case study is also includedPhotovoltaic installations on residential properties gained high momentums during the past decade. Building integrated photovoltaic materials are well developed and has the potential to advance the photovoltaic systems installations on residential and commercial buildings. One of the main limitations on residential system is the utility allowable AC power generation. The installation of BIPV on houses offer numerous orientation and tilts of the PV system which ensure sun energy is harvested for wider timeframe. The different orientations and tilts reflect changes in the generate output power. The available residential inverters have one of two MPPTs which limit the orientation and tilts of the system to a maximum of two options per inverter. Adding more inverters will add cost burden on the system, exceed the utility maximum allowable AC power generation, and additional inverters will not work at rated power throughout the day. The works in this paper include the detail design of a maximum power point box (MPPB) that harvest the sun energy for different orientations and tilts, manage and regulate the DC Bus Bar voltage level as well as generated DC power prior the inverter input terminal. The process is governed by an input from the inverter using an industrial communication protocol such as MODBUS. The aim of the box is to reduce the number of inverters required for maximum power generation while maintaining the maximum AC limits set the by utilities. The paper includes the details design with the proposed circuit along its optimum logics. Case study is also included